CHOOSING THE MOST OPTIMAL WAYS OF WATER DISINFECTION. (World Bulletin of Social Sciences, 2024)
Water disinfection is a critical process to ensure the safety of drinking water. Various methods exist for disinfecting water, each with its advantages and disadvantages. This article explores the most optimal ways of water disinfection by conducting a comparative analysis of commonly used methods, including chlorination, UV irradiation, ozonation, and filtration techniques. The research methods involved a comprehensive literature review to evaluate the effectiveness, cost, environmental impact, and feasibility of each method. The results and discussion section presents the comparative analysis, highlighting the strengths and limitations of each disinfection method. Based on this analysis, conclusions are drawn regarding the most optimal ways of water disinfection for different contexts
Keywords: Water disinfection; chlorination; ozonation; filtration